Answer:
The equation of the line that passes through the point (3,-3) and has a slope of 0 will be:
[tex]0=y+3[/tex]
Step-by-step explanation:
The point-slope form of the equation of a line is:
[tex]\:y\:-\:y_1\:=\:m\left(x-x_1\right)[/tex]
where
As the slope is [tex]m=0[/tex], and the point is [tex](3,-3)[/tex]
so
Equation of the line will be:
[tex]\:y\:-\:y_1\:=\:m\left(x-x_1\right)[/tex]
[tex]y\:-\:\left(-3\right)\:=\:0\left(x-3\right)[/tex]
Further simplifying
[tex]0=y-\left(-3\right)[/tex]
[tex]0=y+3[/tex]
Therefore, the equation of the line that passes through the point (3,-3) and has a slope of 0 will be:
[tex]0=y+3[/tex]